Electrostatic control and the need of feedback control ionization in critical environment of MEMS manufacturing process - Chakkaew, Anusorn; Titiroongruang, Wisut (My University, 2010)
This paper describes new electrostatic control countermeasures and solutions for critical electrostatic control environment that can be implemented in MEMS manufacturing, especially in MEMS's wafer handling that needs low electrostatic voltage. This includes ESD event measurement, machine grounding verification, and low ion imbalance ionization to support current and future needs of the MEMS. Proposed countermeasures are ESD event monitor with electrostatic voltage using a single antenna. Grounding measurement that designed to ignore high-frequency components and measure only the required parameter. These two will help front-end engineer to qualify tools and identify critical process and make the electrostatic issues manageable. Furthermore, the electrostatic field can also be minimized by sub-1 volt ionizer controller that discard initial imbalance, short-term and long-term drift. This brings the balance from 25 volt to sub-1 volt within few second to prevent charge built up in MEMS wafer handling process. ©The Electrochemical Society.